Christian de Chergé: a theology of hope - Salenson, Christian (Cistercian studies series, 2012)
The context -- The conditions of Christian de Chergé's theology -- The foundational experiences -- The place of Islam in God's plan -- The dialogue with Islam -- Reading the Qur'an -- A greater Christ -- Communion of saints and community -- The quasi-sacrament of difference -- Eschatology -- The church of the visitation -- Witness, or, The question of martyrdom -- My brother's keeper -- Praying among others who pray